2021
DOI: 10.3343/alm.2021.41.4.380
|View full text |Cite
|
Sign up to set email alerts
|

Recent Epidemiological Changes in Group B Streptococcus Among Pregnant Korean Women

Abstract: Background Although group B Streptococcus (GBS) colonization rate among pregnant Korean women is lower than that among women from many Western countries, recent data show an upward trend. We investigated recent epidemiological changes in GBS among pregnant Korean women in terms of colonization rate, antimicrobial susceptibility, serotype, and resistance genotype. Methods Vaginal and anorectal swab specimens from 379 pregnant Korean women were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 25 publications
(35 reference statements)
0
23
2
Order By: Relevance
“…The GBS colonization rates among pregnant Korean women ranged from 1.96%–19.8%, and the colonization rate varied depending on the culture medium used, the site of sample collection, and the number of participants. 6 7 16 The US Centers for Disease Control and Prevention (CDC) recommends the use of Todd Hewitt Broth with gentamicin and nalidixic acid (or Lim Broth) to maximize the likelihood of recovering group B streptococci upon plating on sheep blood agar. 17 Swabbing both the lower vagina and rectum (through the anal sphincter) increases the culture yield substantially compared with that obtained by sampling the cervix or the vagina without swabbing the rectum.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The GBS colonization rates among pregnant Korean women ranged from 1.96%–19.8%, and the colonization rate varied depending on the culture medium used, the site of sample collection, and the number of participants. 6 7 16 The US Centers for Disease Control and Prevention (CDC) recommends the use of Todd Hewitt Broth with gentamicin and nalidixic acid (or Lim Broth) to maximize the likelihood of recovering group B streptococci upon plating on sheep blood agar. 17 Swabbing both the lower vagina and rectum (through the anal sphincter) increases the culture yield substantially compared with that obtained by sampling the cervix or the vagina without swabbing the rectum.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, the GBS colonization rate in pregnant Korean women was known to be lower than that in pregnant women from Western countries; however, its prevalence has been increasing recently. 6 7 According to a single medical institution’s longitudinal studies, the colonization rates of GBS in pregnant Korean women were 3.9% in 1993, 8 5.9% in 1995, 9 11.5% in 2008–2009, 10 and 19.8% in 2017–2019. 7 Moreover, an abundance of serotype III and V GBS isolates with multi-drug resistance to clindamycin, erythromycin, and tetracycline has been rapidly increasing in Korea, thus narrowing the choice of therapeutic agents available against infections caused by these serotypes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This method is shown to have a sensitivity and specificity comparable or even better than the standard Lim broth enrichment followed by blood agar cultures (Block et al, 2008, Church et al, 2008. Using the Carrot Broth method, many studies have shown the prevalence of GBS in vaginal swabs in the range of 5 to 19.8% in pregnant women (Choi et al, 2021, Church et al, 2008, Xie et al, 2016. In India, the prevalence of GBS is highly variable depending on the population studied or the methods used.…”
Section: Discussionmentioning
confidence: 99%